1993
DOI: 10.1039/ft9938901351
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacities ofD-mannitol andD-sorbitol in water, dimethyl sulfoxide and formamide

Abstract: Partial molar heat capacities at infinite dilution, C l have been determined calorimetrically for o-mannitol and D-sorbitol in water, dimethyl sulfoxide and formamide, at 298:15 K. The C : values obtained, which are similar for the three solvents, are much higher than the heat capacities for the pure compounds. The large ACZ values for t h e dissolution process are believed to be partly due to t h e existence of several rotamers in solution. Sorbitol seems to be more sensitive than mannitol to specific solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our regression surfaces are in good agreement with values from the literature and differ by DC p,/ /J AE K À1 AE mol À1 ) as follows: glycerol [15], DC p,/ = 3.7; meso-erythritol [15], DC p,/ = 2.5; D-sorbitol [12,13,15,17,19], range (À13.0 6 DC p,/ 6 13.9), average DC p,/ = 3.8; and xylitol [15], DC p,/ = 4.4. Our regression surfaces differ more significantly from those in reference [17]: DC p,/ = À37.7 for meso-erythritol and DC p,/ = À26.7 for xylitol.…”
Section: Table 1esupporting
confidence: 79%
See 1 more Smart Citation
“…Our regression surfaces are in good agreement with values from the literature and differ by DC p,/ /J AE K À1 AE mol À1 ) as follows: glycerol [15], DC p,/ = 3.7; meso-erythritol [15], DC p,/ = 2.5; D-sorbitol [12,13,15,17,19], range (À13.0 6 DC p,/ 6 13.9), average DC p,/ = 3.8; and xylitol [15], DC p,/ = 4.4. Our regression surfaces differ more significantly from those in reference [17]: DC p,/ = À37.7 for meso-erythritol and DC p,/ = À26.7 for xylitol.…”
Section: Table 1esupporting
confidence: 79%
“…The regression surfaces C p,/ (m, T) for equation (4), our observed values of C p,/ (m, T), and literature values of C p,/ (m, T) [12,13,15,17,19] for the seven aqueous polyols are shown in figures 3 to 5. Our regression surfaces are in good agreement with values from the literature and differ by DC p,/ /J AE K À1 AE mol À1 ) as follows: glycerol [15], DC p,/ = 3.7; meso-erythritol [15], DC p,/ = 2.5; D-sorbitol [12,13,15,17,19], range (À13.0 6 DC p,/ 6 13.9), average DC p,/ = 3.8; and xylitol [15], DC p,/ = 4.4.…”
Section: Table 1ementioning
confidence: 96%
“…The alkanediols have wide range of applications in pharmacology and cosmetic industry; however, they are not components of living organisms, but they act as a vehicle for pharmaceuticals or cosmetics when introduced into living organisms [10]. Thus, the properties of amino acids in aqueous-polyols solutions are essential for understanding the chemistry of biological systems [11][12][13] in the presence of these media.…”
Section: Introductionmentioning
confidence: 99%
“…(2) However, we recently observed that C a p, s values for sorbitol (glucitol) and mannitol are about the same for dilute solutions in water, dimethylsulfoxide, and formamide, (4) from which we concluded that our earlier interpretation was not correct. In this paper we report results from heat-capacity measurements on (water + dimethylsulfoxide) and solutions of sorbitol in that solvent mixture.…”
Section: Introductionmentioning
confidence: 78%